Positive and negative experiences with the COVID-19 pandemic among lonely and non-lonely populations in Germany - Wegner, Luisa; Liu, Shuyan (Frontiers in Public Health, 2023)
The COVID-19 pandemic is causing an epidemic of loneliness. Previous studies have shown the differences in positive and negative experiences of lonely and non-lonely people in a non-pandemic setting. However, it is unclear how the drastic alteration of the COVID-19 pandemic may influence peoples’ reactions and beliefs, especially among those who felt lonely. Our study aims to examine the positive and negative experiences among lonely and non-lonely people. We undertook a cross-sectional online survey in the general population in Germany (N = 1758) from May 2020 to May 2022. We assessed their feelings of loneliness with the short 8-item UCLA Loneliness Scale (ULS-8), their positive and negative experience of living in the COVID-19 pandemic as well as their psychological distress regarding the pandemic with the COVID-19 Peritraumatic Distress Index (CPDI). We found lonely individuals (ULS-8 score ≥ 16) reported fewer positive experiences of living in the COVID-19 pandemic, e.g., less time with loved ones (z(1756) = -2.5, p = 0.012) and less sense of togetherness (z(1756) = -2.39, p = 0.017) as compared to non-lonely individuals. Meanwhile, they experienced more negative experiences, e.g., worry and fear (z(1756) = 6.31, p < 0.001) compared with non-lonely individuals. Interestingly, lonely people were less likely to view the pandemic as a conspiracy than non-lonely people were (z(1756) = -3.35, p < 0.001). Our results may give insight into attribution bias and negative affect of lonely people during the COVID-19 pandemic as well as highlight the experience of non-lonely people and raise the question of difference in conspiracy beliefs. For pandemic preparedness and response, decision makers may focus on interventions to foster social cohesion, empower people, build resilience, and most importantly provide timely social care.